An evaluation of different ratio of EFB compost as a growing media for oil palm seedling / Nurul Syuhada Jupery - Jupery, Nurul Syuhada (Faculty of Plantation and Agrotechnology, 2018)
Loss of topsoil due to land degradation could reduce the availability of top soil in Malaysia where there is only unfertile soil left. Furthermore, as increasing in time, the total palm oil mill was also increasing where the EFB contribute 20% from the process of FFB. Unfortunately, the EFB were not fully utilized which create abundance and plenty of oil palm waste. This will contribute to environment pollution and waste disposal problem. Therefore, the use of EFB compost as a growing media for oil palm seedling in pre nursery shows a reliable positive effect in order to manage oil palm waste as well as enrich growing media for oil palm seedling. This study was carried out to determine the efficiency and potential of EFB compost as growing medium for oil palm seedling by using six different ratio of EFB compost (0%, 20%, 40%, 60%, 80% and 100%). Growth performance of palm seedling including plant height, leaf width and leaves length were measured on weekly basis. Meanwhile, the data on plant biomass, root length and soil analysis were conducted at the end of this study at week 10. It was noticed that 80% of EFB compost showed high plant growth performance while the lowest at control treatment (T0). However, ANOVA shows there was no significant different between all treatments (P > 0.05). Soil analysis shows there was no significant difference in soil nutrients except for P availability (P=0.000) at T5. High rate EFB (100%) indicate high nutrient content in growing media. EFB compost has ability to improve soil pH as well as increasing of P availability and exchangeable K, Ca and Mg.